Analisis Jasa Rekening Bersama dalam Keamanan Transaksi Grup Facebook Mobile Legends Ngab-Ngab - Fahlevi, Diega Chandra; Amir, Aprilianto; Suradi (Business Perspective Journal, 2024)
Technological advances allow transactions to be carried out online even though the distance between buyers and sellers is very far, it can also be through used knowed e-commerce to avoid fraud. If the transaction is carried out outside knowed e-commerce will be prone to fraud such as the seller fleeing shortly after the buyer sends money or vice versa the buyer who runs away after the seller sends the goods. With the rise of such fraud cases comes an online service called joint account services. Joint account services are services that bring up third parties who are certainly neutral between buyers and sellers to help secure a transaction. The purpose of this study is to find out how joint account services can improve transaction security. The benefits of this research are expected to help prospective buyers and sellers avoid fraud and introducing joint account services more widely to the public. This research was conducted in one of the Facebook groups called Mobile Legends Ngab-Ngab where online transaction activities which are prone to fraud were frequent. Using qualitative descriptive research methods researchers conduct observations and interviews with informants to find out whether using joint account services can help secure transactions. After conducting observations and interviews with informants, researchers concluded that using joint account services when transactions can increase the security of an online transaction especially by doing Reff status which will be a kind of warranty for buyers. Keywords: joint account, online transaction security, reff, services